Application of Graph Theory in an Intelligent Tutoring System for Solving Mathematical Word Problems. Issue 4 (2016) - Nabiyev, Vasif V.; Çakiroğlu, Ünal; Karal, Hasan; Erümit, Ali K.; Çebi, Ayça
No abstract available